Implementasi Green Economy Terhadap Pembangunan Berkelanjutan dengan Green Growth Policy sebagai Mediasi pada Kota Tebing Tinggi - Arifin, Indra Welly (Economic Development Progress, 2024)
This research is about the Implementation of Green Economy towards Sustainable Development with Green Growth Policy as Mediation in Tebing Tinggi City. This research is quantitative research with a descriptive approach. Data processing in this research uses smartPLS SEM (Partial Least Square - Structural Equation Modeling) software. The research results of the first hypothesis are accepted that Green Economy (X) influences Green Growth Policy (Z). The second hypothesis is accepted that Green Growth Policy (Z) has an effect on Sustainable Development (Y). The third hypothesis is accepted that Green Economy (X) has a significant effect on Sustainable Development (Y) through Green Growth Policy (Z) as an intervening variable.